Women’s representation in Sundanese folklore: A local feminist approach to gender literacy - Sumiyati Sumiyati; S. Sumiyadi S. Sumiyadi; Rudi Adi Nugroho; Halimah Halimah; Yulianeta Yulianeta (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Structural gender inequality persists in Sundanese society despite the cultural philosophy of silih asah, silih asih, and silih asuh, while folklore continues to transmit gender norms across generations. However, studies examining Sundanese folklore through a local feminist perspective to support gender literacy remain limited. This study investigates patterns of women's representation, identifies the local feminist values embedded in four Sundanese folktales (Sangkuriang, Lutung Kasarung, Nyi Pohaci Sanghyang Sri, and Nyi Anteh), and explores their potential contribution to gender-literacy learning within Indonesia's Independent Curriculum. Employing a qualitative descriptive design, the study integrates content and thematic analysis through three coding stages (open coding, focused coding, and thematic synthesis) with credibility enhanced by source triangulation and multi-coder verification. The findings reveal three dialectically interconnected models of women's representation: domestic-submissive, resistant-empowered, and ambivalent figures. These representations embody four interrelated local feminist values: inner fortitude, moral integrity, relational wisdom, and non-confrontational cultural resistance. The study argues that these values constitute an indigenous feminist epistemology that complements and extends dominant Western feminist frameworks by emphasizing culturally embedded forms of agency and resistance. Practically, the findings demonstrate the pedagogical potential of Sundanese folklore as culturally responsive learning materials for fostering students' critical gender literacy, although further classroom-based intervention studies are needed to evaluate their instructional effectiveness.